Relation between Dynamic Characteristics and Parameters of a Two-degree-of-freedom Vibro-impact System with Multi-elastic Constraints. Issue 1 (January 2020) - Yin, Fengwei; Luo, Guanwei
Abstract: A mechanical model of mechanical vibration system with multi-elastic constraints was founded. Based on the multiple parameter and multiple objective cooperative simulation calculation, the three-dimensional parameter space was constructed by the key parameters such as constrained stiffness, excitating frequency and clearance threshold. The large data onto two-dimensional parameter bifurcation diagrams reflecting the correlation between dynamic properties and parameters of the model are obtained. The mode types, existing regions and bifurcation characteristics of periodic impact vibration of the system on the parameter plane of frequency and clearance are described with the change of constrained stiffness. Similarly, the three-dimensional parameter spaced consisting of mass ratio, or damping ratio and excitating frequency and clearance threshold are analyzed. The results show that the high mass ratio excites rich and wonderful periodic vibration, and different damping ratio determines, the bifurcation characteristics and the number of chattering impacts groups in the small frequency domain. The mode types and transition rules of the fundamental periodic impact vibration in small frequency domain and subharmonic impact vibration in high frequency domain induced by different parameters of the system are revealed.